2022
DOI: 10.3390/cancers14205130
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Protein Palladin in Adult Gliomas Predicts Disease Incidence, Progression, and Prognosis

Abstract: Brain tumors comprise over 100 types of masses, differing in the following: location; patient age; molecular, histological, and immunohistochemical characteristics; and prognosis and treatment. Glioma tumors originate from neuroglia, cells supporting the brain. Palladin, a structural protein widely expressed in mammalian tissues, has a pivotal role in cytoskeletal dynamics and motility in health and disease. Palladin is linked to the progression of breast, pancreatic, and renal cancers. In the central nervous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…Gliomas, which account for 3 out of 10 of all brain tumors and 8 out of 10 malignant brain tumors, are adult tumors that develop from the neuroglia, the brain's support cells (1). They encompass malignant brain tumor groups of varying degrees, in which genetic factors affect the development and progression of the disease, and patients have a very short life expectancy after diagnosis (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gliomas, which account for 3 out of 10 of all brain tumors and 8 out of 10 malignant brain tumors, are adult tumors that develop from the neuroglia, the brain's support cells (1). They encompass malignant brain tumor groups of varying degrees, in which genetic factors affect the development and progression of the disease, and patients have a very short life expectancy after diagnosis (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, the roots of the evolution of gliomas can be grouped under two major headings. One is genetic factors like single nucleotide polymorphisms (SNPs), and another is cooperation among environmental elements like lifestyle habits and comorbidities (2,4). Epidemiological studies have identified numerous SNPs, including those in the epidermal growth factor receptor (EGFR) gene, as linked to gliomas (3,5,6).…”
Section: Introductionmentioning
confidence: 99%